2015
DOI: 10.1016/j.polymer.2015.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoimprint lithography on membrane structure and performance

Abstract: a b s t r a c tImparting sub-micron periodic patterns on the surface of ultrafiltration (UF) membranes has been shown to improve their antifouling characteristics. However, the deformation mechanism underlying membrane surface-patterning with nanoimprint lithography (NIL) is currently unclear. In response to this need, this study addresses the influence of nanoimprinting on the structural and performance characteristics of a commercial polyethersulfone (PES) UF membrane. The work utilized a flat (no pattern) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…The pressure measured was 22 MPa and corresponds to the average pressure applied across the membrane. This pressure is much higher than any pressure previously used for nanoimprinting a UF membrane . Apparently, the ability to pattern membrane quickly is due to this high pressure.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The pressure measured was 22 MPa and corresponds to the average pressure applied across the membrane. This pressure is much higher than any pressure previously used for nanoimprinting a UF membrane . Apparently, the ability to pattern membrane quickly is due to this high pressure.…”
Section: Resultsmentioning
confidence: 88%
“…This indicates a significant creep deformation, wherein as the rolling feed velocity is decreased, the time in which the membrane undergoes compression is increasing. Previous research also indicated that increased imprinting duration will decrease the resulting membrane permeance due to increased deformation and loss of porosity. They presented a relationship for creep strain under uniaxial stress for an open‐cell foam that shows an exponential dependence on processing time.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[231] NIL is a lithographic technique which generates polymer nanostructure patterns at high-throughput and precision. [235] Lysozyme and Bacteriophages Modified Membranes: Lysozyme is a nontoxic basic protein found in egg whites, animals, and plant cells with a net positive charge at neutral pH and has an isoelectric point at pH 11. [232] Chou et al were the first to demonstrate the NIL process where they fabricated a pattern of feature size 25 nm and a period of 70 nm in a resist >100 nm and then it was transferred into PMMA using compression moulding.…”
Section: Recent Trends In Surface Modification Strategiesmentioning
confidence: 99%